Innate Immune Network in the Retina Activated by Optic Nerve Crush - Templeton, Justin P. (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. Innate immunity plays a role in many diseases, including glaucoma and AMD. We have used transcriptome profiling in the mouse to identify a network of genes involved in innate immunity that is present in the normal retina and that is activated by optic nerve crush (ONC). METHODS. Using a recombinant inbred (RI) mouse strain set (BXD, C57BL/6 crossed with DBA/2J mice), we generate expression datasets (Illumina WG 6.2 arrays) in the normal mouse retina and 2 days after ONC. The normal dataset is constructed from retinas from 80 mouse strains and the ONC dataset is constructed from 62 strains. These large datasets are hosted by GeneNetwork.org, along with a series of powerful bioinformatic tools. RESULTS. In the retina datasets, one intriguing network involves transcripts associated with the innate immunity. Using C4b to interrogate the normal dataset, we can identify a group of genes that are coregulated across the BXD RI strains. Many of the genes in this network are associated with the innate immune system, including Serping1, Casp1, C3, Icam1, Tgfbr2, Cfi, Clu, C1qg, Aif1, and Cd74. Following ONC, the expression of these genes is upregulated, along with an increase in coordinated expression across the BXD strains. Many of the genes in this network are risk factors for AMD, including C3, EFEMP1, MCDR2, CFB, TLR4, HTA1, and C1QTNF5. CONCLUSIONS. We found a retina-intrinsic innate immunity network that is activated by injury including ONC. Many of the genes in this network are risk factors for retinal disease.